Analysis of Currents in Open Water Southwest of Lae Lae Island - Irwan Anwar Said; Denny Nugroho Sugianto; Muhammad Zainuri; Nur Taufik Syamsudin; Abdul Rasyid Jalil; Ibrahim Ibrahim (CV. Syntax Corporation Indonesia, 2024)
Ocean currents are one of the movements of horizontal or vertical mass movement of seawater that takes place continuously. The purpose of this study is to determine current conditions in open water close to narrow strait waters, as well as canal estuaries. Current data is the result of measurements that have been carried out using ADCP (Acoustic Doppler Current Profiler) mini type ADP-SONTEK equipment on May 16, 2018, while tidal data refers to the recording results of the Makassar BIG tidal station. The results showed that the total surface current speed ranged from 0.017 – 0.375 m/sec with a dominant direction to the west or to open water both at high tide and at low tide. While the result of separation, the speed of tidal currents ranges from 0.032 – 0.343 m / sec.